STORAGE BATTERY CHARGE-DISCHARGE SYSTEM, AND INTERCONNECTION SYSTEM - MATSUMOTO TAKEYUKI (2017)
PROBLEM TO BE SOLVED: To provide a storage battery charge-discharge system capable of accumulating only power generated by a solar battery in a storage battery, and causing a reverse power flow easily at an appropriate time.SOLUTION: A storage battery charge-discharge system charges DC power generated by a recyclable energy generator into a storage battery 7, and discharges DC power stored in the storage battery to a DC/AC converter 2. The system comprises: a current inflow-preventing part D3 for preventing the inflow of power other than DC power generated by the recyclable energy generator 6; a DC/DC converter 12 which operates in a charge mode for charging DC power generated by the recyclable energy generator into the storage battery, and in a discharge mode for discharging DC power from the storage battery to the DC/AC converter through the current inflow-preventing part; and a control circuit 13 which determines an amount of power input to the DC/AC converter, sets the DC/DC converter in the discharge or charge mode, and regulates a voltage output by the DC/DC converter according to the set mode.SELECTED DRAWING: Figure 1 【課題】太陽電池が発電する電力のみを蓄電池に蓄電し、任意の時間に容易に逆潮流できる蓄電池充放電システム。【解決手段】再生可能エネルギー発電装置が発電する直流電力を蓄電池７へ充電し且つ蓄電池に蓄電された直流電力をＤＣ／ＡＣ変換装置２へ放電する蓄電池充放電システムであって、再生可能エネルギー発電装置６が発電する直流電力以外の電力が流入することを阻止する電力流入阻止部Ｄ３、再生可能エネルギー発電装置が発電する直流電力を蓄電池へ充電する充電モードと電力流入阻止部を介して蓄電池からの直流電力をＤＣ／ＡＣ変換装置へ放電する放電モードとで動作するＤＣ／ＤＣ変換装置１２、ＤＣ／ＡＣ変換装置に入力される電力量を判別し、ＤＣ／ＤＣ変換装置を放電モード又は充電モードに設定し、設定されたモードに応じてＤＣ／ＤＣ変換装置が出力する電圧を調整する制御回路１３を備える。【選択図】図１